Review Kurikulum Pendidikan Cara Belajar Siswa Aktif (CBSA) Tahun 1984 dalam Pendidikan Indonesia - Wardhana, Ivan Prapanca (Keraton: Journal of History Education and Culture, 2021)
Curriculum is an essential thing in the implementation of education. Curriculum changes over time are not without clear reasons and foundations, because these changes are driven by the desire to continuously improve, develop, and improve the quality of national education. The National Education Curriculum has undergone changes from 1947 to 2006. The change is a logical consequence of changes in the political, economic and science and technology systems, socio-cultural, in national and state societies. Curriculum 1984 carries the Skill Approachprocess. Although it prioritizes the approach of the process, but the goal factor remains important, this curriculum is also often called "Enhanced 1975 Curriculum" where students are placed in the subject of learning. One of the principles of curriculum development 1984 is the principle of deconcentration which means the division of authority in the development of the curriculum between the center and the region, the regional authority in this case mainly lies in the development of skills in accordance with the development of community culture and employment in the region.